Peripheral sensory function in non‐freezing cold injury patients and matched controls. Issue 3 (20th February 2023) - Wright, Jennifer; Massey, Heather; Hollis, Sarah; Vale, Tom; Bennett, David LH.; Maley, Matthew; Montgomery, Hugh; Tipton, Michael; Eglin, Clare
Abstract : New Findings: What is the central question of this study? Is peripheral sensory function impaired in the chronic phase of non‐freezing cold injury (NFCI)? What is the main finding and its importance? Warm and mechanical detection thresholds are elevated and intraepidermal nerve fibre density is reduced in individuals with NFCI in their feet when compared to matched controls. This indicates impaired sensory function in individuals with NFCI. Interindividual variation was observed in all groups, and therefore a diagnostic cut‐off for NFCI has yet to be established. Longitudinal studies are required to follow NFCI progression from formation to resolution Abstract: The aim of this study was to compare peripheral sensory neural function of individuals with non‐freezing cold injury (NFCI) with matched controls (without NFCI) with either similar (COLD) or minimal previous cold exposure (CON). Thirteen individuals with chronic NFCI in their feet were matched with the control groups for sex, age, race, fitness, body mass index and foot volume. All undertook quantitative sensory testing (QST) on the foot. Intraepidermal nerve fibre density (IENFD) was assessed 10 cm above the lateral malleolus in nine NFCI and 12 COLD participants. Warm detection threshold was higher at the great toe in NFCI than COLD (NFCI 45.93 (4.71)°C vs. COLD 43.44 (2.72)°C, P  = 0.046), but was non‐significantly different from CON (CON 43.92 (5.01)°C, P  = 0.295). Mechanical detection threshold on the dorsum of the foot was higher in NFCI (23.61 (33.59) mN) than in CON (3.83 (3.69) mN, P  = 0.003), but was non‐significantly different from COLD (10.49 (5.76) mN, P  > 0.999). Remaining QST measures did not differ significantly between groups. IENFD was lower in NFCI than COLD (NFCI 8.47 (2.36) fibre/mm 2 vs. COLD 11.93 (4.04) fibre/mm 2, P  = 0.020). Elevated warm and mechanical detection thresholds may indicate hyposensitivity to sensory stimuli in the injured foot for individuals with NFCI and may be due to reduced innervation given the reduction in IENFD. Longitudinal studies are required to identify the progression of sensory neuropathy from the formation of injury to its resolution, with appropriate control groups employed.